2009
DOI: 10.1002/cncr.24605
|View full text |Cite
|
Sign up to set email alerts
|

Combination therapy with rituximab and intravenous or oral fludarabine in the first‐line, systemic treatment of patients with extranodal marginal zone B‐cell lymphoma of the mucosa‐associated lymphoid tissue type

Abstract: Poly(3‐hexylthiophene)‐b‐poly(4‐vinylpyridine) diblock copolymer was synthesized by RAFT polymerization of 4‐vinyl pyridine using a trithiocarbonate‐terminated poly(3‐hexylthiophene) macro‐RAFT agent. The optoelectronic properties and the morphology of the block copolymer blends with CdSe quantum dots were investigated. UV‐vis and fluorescence experiments were performed to prove the charge transfer between CdSe and poly(3‐hexylthiophene)‐b‐poly(4‐vinylpyridine) diblock copolymer. © 2011 Wiley Periodicals, Inc.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(37 citation statements)
references
References 49 publications
0
36
1
Order By: Relevance
“…As opposed to nodal B cell lymphomas, the data on the use of R are relatively scarce. Either R monotherapy or combinations have been tested in patients with MALT lymphoma [9][10][11]. While a randomized trial (published in abstract form) has demonstrated R plus chlorambucil to be more effective than chlorambucil alone, this has not been demonstrated for other chemotherapies and R is currently not approved for application in MALT lymphoma.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…As opposed to nodal B cell lymphomas, the data on the use of R are relatively scarce. Either R monotherapy or combinations have been tested in patients with MALT lymphoma [9][10][11]. While a randomized trial (published in abstract form) has demonstrated R plus chlorambucil to be more effective than chlorambucil alone, this has not been demonstrated for other chemotherapies and R is currently not approved for application in MALT lymphoma.…”
Section: Discussionmentioning
confidence: 98%
“…In case of more advanced disease or in patients failing HP eradication, various systemic forms of treatment have been shown to be active [7][8][9]. While the anti-CD20 antibody rituximab (R) has revolutionized the treatment of various types of B cell lymphomas, the data in patients with MALT lymphoma are still limited [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…The response rate to the combination in this series © F e r r a t a S t o r t i F o u n d a t i o n was excellent, being 100% including 90% CR. 15 Furthermore, the combination of rituximab and chlorambucil has been shown to be highly effective in patients with MALT lymphoma, resulting in response rates of up to 100%, 22,23 even in gastric MALT lymphomas positive for t(11;18)(q21;q21), a known negative predictive marker for response to chlorambucil. [16][17][18] This is not, however, surprising, as it has been shown that the activity of rituximab is not dependent on t(11,18)(q21;q21).…”
Section: © F E R R a T A S T O R T I F O U N D A T I O Nmentioning
confidence: 99%
“…Although its use in MALT lymphoma has not been officially approved for this indication in China, rituximab has been reported to have high effectiveness in this disease, both in monotherapy and in combination immune-chemotherapy (21,33,(39)(40)(41)(42). Furthermore, according to a recent histologic study performed on a patient treated rituximab before receiving thoracic surgery for non-small cell lung cancer, rituximab showed its capability of penetration into lung tissue, and its high efficiency in depleting B cells in normal lung tissue, lung tumor and lung-related LNs (43).…”
Section: Discussionmentioning
confidence: 99%